ETHNO-CONFESSIONAL PICTURE OF ASTRAKHAN ACCORDING TO MATERIALS OF «PHYSICAL» EXPEDITION OF ACADEMY OF SCIENCES 1768-1774 - Mhitaran, Goar Zoraevna (History, Archeology and Ethnography of the Caucasus, 2022)
A number of scientific publications and researches (A.I. Juht, M.M. Imasheva, E.V. Kugrysheva, A.L. Ryabtsev) are devoted to the ethno-confessional image of Astrakhan in the second half of the 18th century but the problem has not been fully solved. In this paper, we aim to recreate the most complete and objective picture of the formation of the ethnic and confessional composition of Astrakhan in the second half of the 18th century and the life of its communities based on materials of the «physical» expedition of the Academy of Sciences in 1768-1774, which previously did not often attract researchers’ attention. The methodological basis of the article was formed by the main principles of historical science: objectivity, scholarship, and historicism, which imply the study of historical events and facts in specific historical conditions. The study showed that the ethno-confessional processes in Astrakhan were greatly influenced by events of foreign policy and trade and economic nature in the region. Astrakhan was the center of international trade, linking Europe with Asia, and European mores and traditions quickly seeped into the city, which absorbed a certain amount of foreign elements. In fact, the materials of the «physical» expedition of the second half of the 18th century were one of the main methods for obtaining new facts and accumulating ethnographic material on the history of Astrakhan communities. Consequently, the research of the Astrakhan expedition of 1768-1774 under the leadership of Academician S. Gmelin is of great significance for studying the ethno-confessional history of Astrakhan and its peoples and the economic prospects of the region with due consideration of the historical peculiarities of the region. And S. Gmelin’s work «Traveling through Russia to Investigate the Three Kingdoms of Nature» takes its rightful place among the primary sources on the history of southern Russia in the second half of the XVIII century.